899 A Closed Loop Audit of Imaging Rate in Suspected Complicated Acute Diverticulitis. (19th August 2022) - Rayner, A; Adepoju, O; Wong, G; Mobasheri, M
Abstract: Aim: Diverticular disease is commonly encountered in western populations, with complicated acute diverticulitis potentially leading to significant morbidity and mortality. The National Institute for Health and Care Excellence (NICE) recommend imaging these patients within 24-hours of admission, which is essential to confirm diagnosis and guide further management. We aimed to audit the imaging rate in suspected complicated acute diverticulitis within our department and identify ways to improve this. Method: Data were collected from all patients admitted from January to June 2021 with suspected complicated acute diverticulitis as defined by NICE. Patients with normal inflammatory markers were excluded. Electronic records were reviewed for evidence of imaging performed within 24-hours of hospital admission and the imaging rate was compared with the previous audit cycle. Results: 96 patients were admitted with suspected complicated acute diverticulitis. 83 patients had raised inflammatory markers. 76 (91.6%) of these had contrast computer tomography (CT) scans performed within 24-hours of admission. Of the 7 (8.4%) patients who did not undergo imaging within 24-hours, 3 had recent imaging suggestive of diverticular disease or diverticulitis, 2 were treated with antibiotics, 1 patient refused, and 1 had CT within 48-hours due to delays waiting for dialysis. Conclusions: We have shown continued good compliance with NICE guidelines, though the imaging rate has declined slightly compared with the previous audit cycle (94.3%). In order to maintain and improve these standards, we will offer educational sessions within our department to underline the importance of timely imaging in this patient group and continue to audit our performance.